1977
DOI: 10.1111/j.0954-6820.1977.tb16837.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Turnover in Renal Cysts

Abstract: Cystic puncture was performed percutaneously in 18 patients with solitary renal cysts and in 22 with multiple, congenital renal cysts. With the aid of tritiated water it was possible to estimate the fluid turnover in the cysts and compare it with their volume, pressure and potassium and creatinine levels. Fluid turnover was rapid in all the renal cysts. Two to five hours after i. v. injection of tritium, the tritium concentration in cystic fluid averaged 88% of the concentration in plasma fluid in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…A study in 1977 using tritiated water shows a high turnover of cyst fluid in ADPKD (.100 ml in 24 hours for a 10-ml cyst) thought to be secondary to active solute transport and therefore, susceptible to pharmacotherapy. 82 Studies using polarized normal human kidney and ADPKD cells on permeable supports and microcysts in hydrated collagen confirm a model of fluid transport as previously shown in MDCK cells and other secretory epithelia. 83 Intact cysts excised from ADPKD kidneys secrete fluid when treated with forskolin, confirming that intact cyst epithelia secrete fluid by mechanisms regulated by cAMP.…”
Section: Fluid Secretionsupporting
confidence: 78%
“…A study in 1977 using tritiated water shows a high turnover of cyst fluid in ADPKD (.100 ml in 24 hours for a 10-ml cyst) thought to be secondary to active solute transport and therefore, susceptible to pharmacotherapy. 82 Studies using polarized normal human kidney and ADPKD cells on permeable supports and microcysts in hydrated collagen confirm a model of fluid transport as previously shown in MDCK cells and other secretory epithelia. 83 Intact cysts excised from ADPKD kidneys secrete fluid when treated with forskolin, confirming that intact cyst epithelia secrete fluid by mechanisms regulated by cAMP.…”
Section: Fluid Secretionsupporting
confidence: 78%
“…[ 7 , 22 , 23 ] However, the reported recurrence rate is still up to 19%, regardless the technique used. [ 12 ] Jacobsson et al [ 24 ] have shown that secretory activity of the remaining cyst wall after unroofing may play a causal role in cystic recurrence. If the resection of such a wall is incomplete, the residual secreting cyst wall can become adherent to surrounding tissues with the development of a new cyst.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The problem with simple aspiration is the high recurrence rate because the epithelium of cysts can rapidly produce more fluid and refill the cyst. 35 Recurrence of renal cysts after simple aspiration occurs in anywhere from 30 to 100% of cases in the series reported. [36][37][38][39] For this same reason, simple catheter drainage is rarely used.…”
Section: Renal Cystsmentioning
confidence: 99%